PUBLIC NARRATIVE OF SMART COMMUNITY-BASED TOURISM IN MAGELANG REGENCY - Chusnul Azizah Indahsari; Prihatin Dwihantoro (FAKULTAS DAKWAH UIN SALATIGA, 2023)
Tourism development is one of the government's flagship programs in regional development today. Magelang Regency is one of the areas that has become a point of government attention in the progress of smart community-based tourism development. This study aims to determine whether the new concept has reached the community and is implemented in the tourism sector of Magelang district. The researcher uses an explanatory qualitative method using Habermas' action communication theory to analyze this study. This program as one of the tourism sustainability programs creates a smart community that capable of digital literacy, particularly the tourism movement. However, the program needs precise and widespread delivery to the community that will be known and easy to implement. The success of this program has been found but discourse, narrative, or public opinion yet here on social media regarding the smart community-based tourism program, so this program seems to be running independently.